1955
DOI: 10.1172/jci103200
|View full text |Cite
|
Sign up to set email alerts
|

Hematogenous Pyelonephritis in Rats. I. Its Pathogenesis When Produced by a Simple New Method 12

Abstract: The study of experimental pyelonephritis has been generally restricted to that form of the disease which develops after ligation of the ureter (1-3). When pyelonephritis is complicated by ureteral ligation, however, a clear distinction cannot be made between the effects of urinary obstruction and those of infection. We have attempted, therefore, to establish experimental pyelonephritis in the absence of hydronephrosis and have succeeded by subjecting rats to a simple new technique requiring only two steps: 1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0

Year Published

1957
1957
1988
1988

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(27 citation statements)
references
References 4 publications
(5 reference statements)
1
26
0
Order By: Relevance
“…Furthermore, as expected from the gross appearance of the lesions at 1 and 2 weeks, the histological data indicated that the rare lesions in Group II kidneys were small and showed minimal extension through the kidney parenchyma. whereas lesions in Group I presented the typical wedge-shaped appearance described in previous studies (13,16 fold. Blood levels of E. coli were virtually identical in both groups at 24 hours and were negative by 1 week.…”
supporting
confidence: 65%
“…Furthermore, as expected from the gross appearance of the lesions at 1 and 2 weeks, the histological data indicated that the rare lesions in Group II kidneys were small and showed minimal extension through the kidney parenchyma. whereas lesions in Group I presented the typical wedge-shaped appearance described in previous studies (13,16 fold. Blood levels of E. coli were virtually identical in both groups at 24 hours and were negative by 1 week.…”
supporting
confidence: 65%
“…Immediately afterward, each rat was inoculated intracardially with 0.5 ml of an 18-hour culture in trypticase soy broth containing approximately 109 cells per ml of the same E. coli strain from which the endotoxin had been extracted. The kidneys of the animals were massaged for 5 minutes through the intact abdominal wall in order to produce pyelonephritis (27). Seven days later all surviving rats were sacrificed by exsanguination and exposure to ether.…”
Section: Preparation and Properties Of An Imnlimunsogenic Endotoxin Omentioning
confidence: 99%
“…Furthermore, many experimental techniques induce haematogenous pyelonephritis, 43 whereas most natural infections are ascending in nature. The interventional techniques have included administration of renal toxins (Yamauchi et at., 1961), potassium depletion (Woods et at., 1960), electrocautery (Rocha et at., 1958), renal massage (Braude, Shapiro & Siemienski, 1955), ureteric occlusion (Lepper, 1921), occlusion of renal arteries (Goldblatt et at., 1934), challenge with highly virulent bacteria (Cotran et at., 1963) and foreign-body implantation (Miller et at., 1956). The routes of bacterial challenge have included intravenous (Helmholz, 1934), intracardiac (Pitsch, Hebert &Carey, 1962) andintra-urethral (Hepinstall, 1965) injection, and the introduction of infection directly into the bladder (Brooks, Lyons & Braude, 1974) or kidney (Alderman & Freedman, 1963).…”
Section: Discussionmentioning
confidence: 99%